EXPERIENCE OF USING BLACKBOARD E-LEARNING SYSTEM PLATFORM IN BACHELORS TRAINING - Alexey I. Nazarov; Olga V. Sergeeva (Открытое образование (Москва))
The approaches to organization and tracking of educative process by means of distant learning technologies are considered. The article provides description and approbation results of network educational module «Mechanics and Molecular Physics», carried out on Blackboard e-learning system. The article describes the overall results of teaching process. The authors present the platform advantages in organizing and tracking of students self-directed learning.